The Research and the Arts Practice - A Symbiotic Liaison? - Abdullah, Sarena (Petronas, Kuala Lumpur, 2011)
When writing about art, besides doing a formal descriptive analysis, there are various ways in which we can derive meaning and understanding of artworks. For example, through discussing the subject matter of the work, the study of iconography and iconology of objects/subjects, and recently through Critical Theories such as feminism, semiotics, post-structuralism, deconstruction, psychoanalysis and postmodernism to name a few!Through various publication opportunities, art writers and art critics should seek either book chappters, journals, peer-reviewed journals for example, to write and print an extended, in-depth essay grounded in proper research writing.